2002
DOI: 10.1113/jphysiol.2002.017426
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin (orexin) enhances neuron activity and cell synchrony in developing mouse GFP‐expressing locus coeruleus

Abstract: The noradrenergic neurons of the locus coeruleus (LC) play an important role in modulating arousal and selective attention. A similar function has been attributed to the hypocretin neurons of the hypothalamus which maintain a strong synaptic projection to the LC. As the LC can be difficult to detect in the embryonic and neonatal mouse brain, we used a new transgenic mouse with strong GFP expression in the LC under the regulation of a mouse prion promoter. GFP colocalized with immunoreactive tyrosine hydroxylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(76 citation statements)
references
References 56 publications
7
69
0
Order By: Relevance
“…5). These results build upon previous in vivo electrophysiological experiments demonstrating that Hcrts depolarize LC neurons (12,18,31) and increase LC discharge rates (12,17,(19)(20)(21). We conclude that the LC gates Hcrt-mediated sleep-to-wake transitions during NREM sleep and serves as a necessary downstream effector for Hcrt function in promoting arousal.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…5). These results build upon previous in vivo electrophysiological experiments demonstrating that Hcrts depolarize LC neurons (12,18,31) and increase LC discharge rates (12,17,(19)(20)(21). We conclude that the LC gates Hcrt-mediated sleep-to-wake transitions during NREM sleep and serves as a necessary downstream effector for Hcrt function in promoting arousal.…”
Section: Discussionmentioning
confidence: 58%
“…To gain insight into the effects of Hcrt stimulation on LC membrane potential, we built a minimal realistic model of Hcrt-LC circuitry, using previous biophysical studies (18,29,31). Our model focuses on the effect of Hcrt activity on downstream LC neurons, showing that Hcrt stimulation slowly (over several seconds) increases the membrane potential of LC neurons from baseline (<1 Hz) to tonic discharge (1-3 Hz) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For FRIL, P7-P21 and adult Sprague-Dawley rats were obtained from Laboratory Animal Services at Colorado State University. In addition, mice whose LC neurons express Enhanced Green Fluorescent Protein (EGFP) (van den Pol et al, 2002) were obtained from a colony established courtesy of Anthony N. van den Pol, Yale University School of Medicine, New Haven, CT.…”
Section: Experimental Procedures Animalsmentioning
confidence: 99%
“…After this epoch-making discovery, a whole series of studies confirmed that the orexin system plays a central role in the regulation of sleep/wakefulness. Neurons expressing orexin (orexin neurons) activate nuclei considered wake-promoting, including LC noradrenergic neurons (Horvath et al, 1999;van den Pol et al, 2002), raphe serotonergic neurons Liu et al, 2002), TMN histaminergic neurons Yamanaka et al, 2002), and PPT/LDT and basal forebrain cholinergic neurons Eriksson et al, 2001). Central administration of orexin-A in rodents reduces REM and non-REM sleep, and increases wakefulness time (Hagan et al, 1999).…”
Section: Mmandtsmentioning
confidence: 99%